2016
DOI: 10.1136/annrheumdis-2016-209522
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in juvenile-onset mixed connective tissue disease: a nationwide Norwegian study

Abstract: Most patients with JMCTD had active disease and organ damage after a mean follow-up of 16.2 years. Active disease was associated with higher anti-ribonucleoprotein antibody levels and positive RF. The presence of RF at diagnosis predicted persistent disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
2
25
0
3
Order By: Relevance
“…Hetlevik et al [19] reported presence of fever at the onset of the disease in 29% of children, arthritis in 94% of children, presence of rheumatoid factor in 64%, edema in hands in 77%, weakening of muscles in over 40%, sclerodactyly in 10%, lung function impairment in 58% of children. 15% of children had remission, active disease was diagnosed in 67%.…”
Section: Resultsmentioning
confidence: 99%
“…Hetlevik et al [19] reported presence of fever at the onset of the disease in 29% of children, arthritis in 94% of children, presence of rheumatoid factor in 64%, edema in hands in 77%, weakening of muscles in over 40%, sclerodactyly in 10%, lung function impairment in 58% of children. 15% of children had remission, active disease was diagnosed in 67%.…”
Section: Resultsmentioning
confidence: 99%
“…The main strength of our study was that it was the first to compare juvenile MCTD patients with a control group. It was also the largest study to assess HRCT and PFT systematically in all patients, and the cohort is believed to be representative of juvenile MCTD patients living in Norway, as described in more detail previously (17). Progression of pulmonary manifestations in juvenile MCTD patients has not previously been reported, and we had a long follow-up of 16.2 years from the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were identified through multiple acquisition routes and a nationwide approach, identification and inclusion have been described in detail previously (17). Sixty two patients were initially identified, of these patients three were deceased, three did not wish to participate, one did not respond to our enquiries, and three had developed clinical SLE and were excluded.…”
Section: Patients and Controlsmentioning
confidence: 99%